Capital market integration : capital controls and exchange rate stability - Worrell, Delisle (1998)
Suggests that capital controls are not a significant barrier to regional investment in the Caribbean. Argues that some types of control contribute to the efficiency of the market for foreign exchange, and should be retained and contrasts those with controls which distort markets. Concludes that countries with capital controls, implementing Protocol II of the Caribbean Community Treaty effectively remove these controls, even those that are beneficial. Suggests therefore, that it is not appropriate to implement Protocol II at this time.